2023
DOI: 10.1007/s00423-023-02992-4
|View full text |Cite
|
Sign up to set email alerts
|

Textbook outcome contributes to long-term prognosis in elderly colorectal cancer patients

Abstract: Textbook outcome (TO) has been used to de ne achievement of multiple "ideal" or "optimal" surgical and postoperative quality measures from the patient's perspective. However, TO has not been reported for their impact on survival in elderly, including CRC surgery. This study determined whether TO is associated with long-term outcomes after curative colorectomy in patients with colorectal cancer (CRC). MethodsPatient who underwent curative surgery over 75 years old for CRC between March 2005 and December 2016. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 1[6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Twelve studies (70.6%) have been published in the last 3 years and 94.1% in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the included studies are shown in Table 1[6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Twelve studies (70.6%) have been published in the last 3 years and 94.1% in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…example, studies focusing on the elderly patients found lower textbook outcome values (43-68%)[10,11,13,19,23]; however, Taffurelli et al found that biological age did not correlate as well as patient frailty. In this study, a score ≥ 2 on the Flemish version of the Triage Risk Screening Tool (fTRST) had an increased risk of worse postoperative outcomes (Odds Ratio 1.97; 95% CI: 1.23-3.16)[13].…”
mentioning
confidence: 97%
“…Consequently, the percentage of successfully achieved TO is notably higher, observed in 77.4% of the patients [ 13 ]. Certain authors emphasize the lack of a stoma post-surgery to be a crucial component of TO [ 14 ]. However, in high-risk low anastomosis cases, a preventive ileostomy is typically instituted as a standard preventive measure against anastomotic leakage or to minimize potential damage from such leakage.…”
Section: Discussionmentioning
confidence: 99%